2020
DOI: 10.1186/s40729-020-00211-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and patient-reported outcome of implant restorations with internal conical connection in daily dental practices: prospective observational multicenter trial with up to 7-year follow-up

Abstract: Background: The interpretation of the results of randomized clinical trials is often questioned in relation with daily circumstances in practices. This prospective observational multicenter study was instigated to reflect the need for information in real-life situations with dental implants with internal conical implant-abutment connection (Conelog implant system). The implants were followed up at least 5-year post-loading; survival analysis (Kaplan-Meier), changes of soft tissue, and bone level over time, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Similar studies also reported high patient satisfaction with implant restorations in partially dentated arches. [40][41][42] Considering the strengths and limitations of this study, despite its relatively small sample, the reported long-term data can provide valuable information regarding the use of dental implants with intraoperatively conditioned hydrophilic surfaces in an early loading scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies also reported high patient satisfaction with implant restorations in partially dentated arches. [40][41][42] Considering the strengths and limitations of this study, despite its relatively small sample, the reported long-term data can provide valuable information regarding the use of dental implants with intraoperatively conditioned hydrophilic surfaces in an early loading scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all implants were in function for a mean duration of approximately 3 years, which is a relatively short duration. Studies [2,44,45] have shown that under physiologic conditions dental implants demonstrate minimal CBL up to 7 years of PL. The authors applaud results reported in a non-interventional multicenter study [45] according to which, dental implants placed in individuals (mean age approximately 50 years) demonstrate CBL of 0.52 ± 0.55 mm after 36 months of PL.…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight different prosthetic joint connections have been considered: internal hexagonal joint 1 mm below the bone level position [19][20][21][22][23][24][25][26][27], internal hexagonal joint at bone level position [19], external hexagonal joint at bone level position [23,25,26,[28][29][30][31], Internal conical prosthetic joint with index [19,22,27,28,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], cone morse 1 mm below the bone level position [23][24][25][26]30,[47][48][49], cone morse at the bone level position [49], 1). A total of eight different prosthetic joint connections have been considered: interna...…”
Section: General Parametersmentioning
confidence: 99%